State Defense: Challenges Towards Digitalization - Ni Ketut Tri Srilaksmi; Bernika Irnadianis; Dwi Estiningtyas; Maria Delareiza; Sulistiowati Sulistiowati; Ajeng Nilam (Journal of Digital Law and Policy, 2023)
Indonesia's national resilience is a dynamic condition of a nation or Indonesia which includes all integrated national life containing tenacity and resilience which contains the ability to develop national strength in facing and overcoming all challenges, threats, obstacles and disturbances, both coming from within and from outside, to ensure identity and integrity. Thus, national resilience is the ability of a nation to maintain its unity and integrity, strengthen its life support capacity, face all forms of threats it faces so that it is able to carry on its life in achieving the welfare of the nation in this digital era. National Resilience is abbreviated as Tannas (Ketahanan Nasional). Efforts to organize national resilience can be realized by defending the state. State defense is the attitude and behavior of citizens who are inspired by their love for the Unitary State of the Republic of Indonesia based on Pancasila and the 1945 Constitution in establishing the survival of the nation and state as a whole. Every citizen has the right and is obliged to participate in the defense of the state and the conditions for defense are regulated by law. Awareness of defending the country is essentially a willingness to serve the country and a willingness to sacrifice to defend the country.